Transplanting colonies of Cladophora crispata susceptible to die to increase the available biomass: Strategy for sustainability and food security in Lake Titicaca - Canales-Gutiérrez, Ángel (2021)
The algae Cladophora crispata “Llaska” is an important food species for populations that live around of Lake Titicaca. However, its biomass is affected for level decreasing of Lake Titicaca. Therefore, the aims were to determine the fresh Llaska biomass in the rainy and dry season on three communities around the lake and to assess the level success of Llaska colonies transplanted to increase the available biomass. The biomass assessment was using a 0.25 cm side metal quadrant. For transplanting Llaska colonies susceptible to die were used, which were distributed in rows at 10 m from the lake shore. The highest biomass was found in the rainy season, particularly in March (785.28 ± 89.98 g/m2). The biomass was similar between the three study areas, although it was high in Llachon community. Transplant of Llaska colonies was successful, since both the colonies height and diameter increased during the assessment time. In particular, Llaska height had the greatest response during the evaluation time. Therefore, with the transplantation of dying colonies we could increase the biomass available to food purposes.